Persepsi Masyarakat Desa Balamoa Kabupaten Tegal Terhadap BMT Mitra Bersama Kabupaten Tegal Dalam Pemberdayaan Ekonomi Masyarakat - Fatikha, Naeli; Tubagus Surur, Achmad; Tamamudin (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2024)
This study aims to determine the perceptions of the people of Balamoa Village, Tegal Regency towards BMT Mitra Bersama, Tegal Regency in carrying out community economic empowerment. This research uses a qualitative method. The data collection method in this study was obtained from interviews and direct observation as primary data. The secondary data was obtained from various literature such as journals, books, and other relevant references. This research was conducted in Balamoa Village, Tegal Regency and BMT Mitra Bersama Tegal Regency from 15 June 2023 to 28 June 2023. The results showed that the community's perception of BMT Mitra Bersama Tegal Regency showed good results, they assessed the contribution of BMT to community economic empowerment which is carried out through financing and savings is quite positive and efficient considering that BMT Mitra Bersama Tegal Regency gives priority to people whose economies are in the lower middle class. This can be seen from the increase in the income of members who make financing or savings. In addition, they claim that the socialization and promotion of BMT Mitra Bersama in Tegal Regency is quite good, the products provided are also very varied so that they can be selected according to the needs of their members.